Partial homonymous hemianopia of traumatic origin after riding a high-speed amusement ride - Hohberger, B.; Trollmann, Regina; Rompel, O.; Gölitz, Philipp; Gusek-Schneider, G. C. (Ophthalmologe, 2016)
Amusement park injuries have become more common in recent years. Especially neurological symptoms dominate clinical findings. In this article, the case of a 15-year-old child with homonymous hemianopia due to an atypical intracranial bleeding with subdural hematoma after a giant swing ride is described for the first time.
EVALuna2:21326